Abundance and Phylogenetic Affiliation of Iron Reducers in Activated Sludge as Assessed by Fluorescence In Situ Hybridization and Microautoradiography - Nielsen, Jeppe Lund (American Society for Microbiology, 2002)
Microautoradiography (MAR) was used to enumerate acetate-consuming bacteria under Fe(III)-reducing conditions in activated sludge. This population is believed to consist of dissimilatory iron-reducing bacteria, because the applied incubation conditions and the use of specific inhibitors excluded consumption of radiolabeled acetate by other physiological groups such as sulfate reducers. By use of this approach, dissimilatory iron reducers were found in a concentration of 1.1 × 10(8) cells per ml, corresponding to approximately 3% of the total cell count as determined by DAPI (4′,6′-diamino-2-phenylindoledihydrochloride-dilactate) staining. The MAR enumeration method was compared to the traditional most-probable-number (MPN) method (FeOOH-MPN) and a modified MPN method, which contains Ferrozine directly within the MPN dilutions to determine the production of small amounts of ferrous iron (Ferrozine-MPN). The Ferrozine-MPN method yielded values 6 to 10 times higher than those obtained by the FeOOH-MPN method. Nevertheless, the MAR approach yielded counts that were 100 to 1,000 times higher than those obtained by the Ferrozine-MPN method. Specific in situ Fe(III) reduction rates per cell (enumerated by the MAR method) were calculated and found to be comparable to the respective rates for pure cultures of dissimilatory iron-reducing bacteria, suggesting that the new MAR method is most reliable. A combination of MAR and fluorescence in situ hybridization was used for phylogenetic characterization of the putative iron-reducing bacteria. All activated-sludge cells able to consume acetate under iron-reducing conditions were targeted by the bacterial oligonucleotide probe EUB338. Around 20% were identified as gamma Proteobacteria, and 10% were assigned to the delta subclass of Proteobacteria.